Implementation of inventory management in footwear industry - Jeferson Conceiç\~ao; José de Souza; Elton Gimenez-Rossini; Alfonso Risso; Alexandre Beluco (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The objective of this research was to implement new inventory management in a footwear company through the analysis of indicators obtained from inventory data collection. Design/methodology/approach: The methods of ABC analysis, demand forecasting, safety stock, reorder point and economic order quantity were applied. The items in inventory were classified by order of financial importance through ABC analysis, and the proposed indicators were analyzed to determine the moment the inventory replenishment should be carried out as well as the purchase lot size for each item. The research also analyzed the behavior of the demand and pointed out the demand forecasting method that came closest to reality. Findings: The study presents a method of implementing inventory management based on indicators derived from the application of ABC curve methods, demand forecasting, safety stock, re-fulfillment point, and economic purchased lot. It also indicates how the ABC classification of stocks can be used to check the most representative materials in stock. The study also highlights that the rejection of modifications can be surpassed by obtaining favorable results. Research limitations/implications: The inventory management applied in this work is based on indicators that resulted in two main data which were able to define the size of the purchase lot to be ordered and the amount of material needed. Practical implications: The methods of ABC analysis, demand forecasting, safety stock, reorder point and economic order quantity were applied. The items in inventory were classified by order of financial importance through ABC analysis, and the proposed indicators were analyzed to determine the moment the inventory replenishment should be carried out as well as the purchase lot size for each item. The research also analyzed the behavior of the demand and pointed out the demand forecasting method that came closest to reality. Originality/value: In this study, a method applied is presented, highlighting the importance of the methodological application for the implementation of inventory management. The study contributes to the encouragement and adoption of methodologies to improve analysis and inventory management in companies.
Keywords: 650; demand forecasting; inventory; ABC analysis; reorder point